2020
DOI: 10.7717/peerj.8680
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding proteins involved in regulation of protein synthesis to initiate biogenesis of secondary tumor in hepatocellular carcinoma in mice

Abstract: Background The tumor microenvironment (TM) in close contact with cancer cells is highly related to tumor growth and cancer metastasis. This study is to explore the biogenesis mechanism of a secondary hepatocellular carcinoma (HCC) based on the function of RNA binding proteins (RBPs)-encoding genes in the physiological microenvironment (PM). Methods The healthy and HCC mice were used to isolate the PM, pre-tumor microenvironment (PTM), and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…RNA-binding proteins are also inextricably linked with HCC. Li et al (2020) found that RNA-binding proteins help transform the physiological microenvironment into the tumor microenvironment by regulating protein synthesis, thus initiating the biogenesis of secondary mouse HCC. PIWIL1 (also known as HIWI) is a member of the PIWI subfamily.…”
Section: Piwi-interacting Rnas and Hepatocellular Carcinomamentioning
confidence: 99%
“…RNA-binding proteins are also inextricably linked with HCC. Li et al (2020) found that RNA-binding proteins help transform the physiological microenvironment into the tumor microenvironment by regulating protein synthesis, thus initiating the biogenesis of secondary mouse HCC. PIWIL1 (also known as HIWI) is a member of the PIWI subfamily.…”
Section: Piwi-interacting Rnas and Hepatocellular Carcinomamentioning
confidence: 99%
“…In this analysis, we looked at both gene up-regulation and spliced genes in the livers of NDEA-treated mice and found 321 controlled groups in the GOMolFn of early tumorigenesis in att-myc mice treated with NDEA, with the top 30 up-regulation groups discussed in Table 7. The upregulation of RNA binding to protein involved in the regulation of protein synthesis to initiate biogenesis of the secondary tumor in hepatocellular carcinoma in mice [23].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred healthy mice aged 6-8 weeks and weighing 25-30 g were used to construct the mouse model of HCC according to the previous method in our laboratory. 11 The tumor tissues (set up as group “H”) and paracancerous liver tissues (set up as group “C”) were collected separately, as well as liver tissues from control mice injected with saline (set up as group “OO”). Three biological replicates of 100 mg of each sample were taken, and total RNA was extracted using a RNA extraction kit and sent to BGI Genomics Co., Ltd. (hereinafter referred to as “Huada Gene”).…”
Section: Methodsmentioning
confidence: 99%